Development of software defined radio modem for satellite ground station - Low, Ai Ning (Nanyang Technological University, 2024)
A key component of the ground station are modems that are used to process Radio Frequency signals from satellites that are received by the antennas, before transmission to the backend infrastructure. With more satellites in orbit, ground stations are required to communicate with multiple satellites using different signal modulation schemes. Instead of multiple traditional modems, a single software defined radio modem allows the user to reconfigure the modem for each satellite, enabling more flexibility and lowering cost. The objective of this project is to develop a flexible ground station modem using software defined radio.